The Roles of Dai and Pastors in Preventing Negative Speech in the Community of Badar District, Southeast Aceh Regency - Tony Gunawan Aroean; Hardiansyah Hardiansyah; Suraiya IT (LaKaspia, 2025)
Badar District is a border area characterized by a plural society where both Muslim and Christian communities coexist in relatively equal proportions. This socio-religious diversity places religious leaders such as dai and pastors in a crucial position to promote harmony and prevent social tension. This study aims to analyze the roles of dai and pastors in preventing negative speech within the community of Badar District, Southeast Aceh Regency. The research employed a qualitative field research approach, with data collected through observation, in-depth interviews, and documentation. The data were analyzed descriptively with an emphasis on social meaning and contextual interpretation. The findings reveal that both dai and pastors play a significant role in preventing the use of negative speech that could potentially trigger social conflict. Dai utilize sermons, religious study sessions, and preaching training to instill polite communication ethics, while pastors employ weekly homilies, pastoral counseling, and interfaith moderation programs to foster mutual respect among different faith groups. These collaborative efforts have successfully raised public awareness of the importance of maintaining ethical speech, strengthening interfaith dialogue, and reinforcing social cohesion in the multicultural context of Southeast Aceh.